Gender Transformative Approach (GTA) Implementation for SAPLING and Sustainable Intensification Initiatives in Ethiopia - Nemera, Martha; Najjar, Dina; Tsige, Meseret; Alma, Eileen (2024)
Interventions that use innovations for food security and livelihoods are expected to either benefit, reach, empower or transform local people’s social and economic status. Gender Transformative Approach (GTA) is a move beyond empowerment for transforming unequal gender power relations and structures that perpetuate and sustain gender inequalities (Hillenbrand, Karim, Mohanraj, & Wu, 2015). GTA explores, questions, and transforms the root causes of gender inequalities that exist in discriminatory norms, structures, policies, and institutions (FAO, IFAD, & WFP., 2022). Since patriarchal gender norms and values are the root causes of gender inequalities in developing countries (Jayachandran, 2015), GTA focuses on transforming these patriarchal gender norms that are embedded in everyday life, discriminatory laws, structures, and policies.